The Trump Effect: How 2016 Campaign Rallies Explain Spikes in Hate - Feinberg, Ayal; Branton, Regina; Martinez-Ebers, Valerie (PS, political science & politics, 2022)
The 2016 Trump campaign held more than 300 rallies. Our research examines whether these rallies and Trump’s rhetoric served as opportunities for the spread of hate. We measured the number of reported white-supremacist propaganda, anti-Semitic incidents, and extremist behaviors that occurred both leading up to and directly following these campaign events. We contend that Trump’s rhetoric and rallies increased the perceived threat facing white Americans, heightening their white identity, all while justifying violence and extralegal methods to address their grievances and thereby increasing reported bias incidents. We find that counties that hosted a Trump rally experienced an increase in hate-motivated events. We systematically show that Trump political rallies were associated with a limited size but significant rise in the likelihood of reported hate and bias incidents.